2021
DOI: 10.1007/s00167-021-06651-3
|View full text |Cite
|
Sign up to set email alerts
|

A high rate of talocalcaneal interosseous ligament tears was found in chronic lateral ankle instability with sinus tarsi pain

Abstract: Purpose To evaluate the arthroscopic indings of subtalar joints, including interosseous talocalcaneal ligament (ITCL) tear, in patients with chronic lateral ankle instability (CLAI) and sinus tarsi pain. Methods A total of 118 ankles (109 patients) having CLAI with sinus tarsi pain who had undergone subtalar arthroscopy and lateral ankle ligament surgery were evaluated. The medical records, radiologic images, and the arthroscopic images and videos were reviewed. ITCL tears were classiied into 4 grades: grade 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Subtalar joint instability is an entity commonly neglected within the scope of lateral ankle instability in patients of all ages; up to 25% of chronic ankle instabilities have associated subtalar instability [ 2 , 24 , 30 ], which could account for some of the cases with persistent symptoms after isolated repair or reconstruction of the anterior talo-fibular ligament [ 38 ]. A recent study found 90% of patients with chronic lateral ankle instability and sinus tarsi pain had ITCL tears [ 36 ]. Patients complain of giving way of the ankle, especially over irregular terrain or during athletic activity, and report pain on the lateral side of the hindfoot and the sinus tarsi.…”
Section: Introductionmentioning
confidence: 99%
“…Subtalar joint instability is an entity commonly neglected within the scope of lateral ankle instability in patients of all ages; up to 25% of chronic ankle instabilities have associated subtalar instability [ 2 , 24 , 30 ], which could account for some of the cases with persistent symptoms after isolated repair or reconstruction of the anterior talo-fibular ligament [ 38 ]. A recent study found 90% of patients with chronic lateral ankle instability and sinus tarsi pain had ITCL tears [ 36 ]. Patients complain of giving way of the ankle, especially over irregular terrain or during athletic activity, and report pain on the lateral side of the hindfoot and the sinus tarsi.…”
Section: Introductionmentioning
confidence: 99%